Antimicrobial Activity and Phytochemical Analysis of Organic Extracts from Cleome spinosa Jaqc. - Silva, Ana P. Sant'Anna da; Nascimento da Silva, Luís C.; Martins da Fonseca, Caíque S.; de Araújo, Janete M.; Correia, Maria T. dos Santos; Cavalcanti, Marilene da Silva; Lima, Vera L. de Menezes (Frontiers in Microbiology, 2016)
Due to the use of Cleome spinosa Jacq. (Cleomaceae) in traditional medicine against inflammatory and infectious processes, this study evaluated the in vitro antimicrobial potential and phytochemical composition of extracts from its roots and leaves. From leaves (L) and roots (R) of C. spinosa different extracts were obtained (cyclohexane: ChL and ChR; chloroform: CL and CR; ethyl acetate: EAL and EAR, methanol: ML and MR). The antimicrobial activity was evaluated by the broth microdilution method to obtain the minimum inhibitory (MIC) and microbicidal (MMC) concentrations against 17 species, including bacteria and yeasts. Additionally, antimicrobial and combinatory effects with oxacillin were assessed against eight clinical isolates of Staphylococcus aureus. All C. spinosa extracts showed a broad spectrum of antimicrobial activity, as they have inhibited all tested bacteria and yeasts. This activity seems to be related to the phytochemicals (flavonoid, terpenoids and saponins) detected into the extracts of C. spinosa. ChL and CL extracts were the most actives, with MIC less than 1 mg/mL against S. aureus, Bacillus subtilis and Micrococcus luteus. It is important to note that these concentrations are much lower than their 50% hemolysis concentration (HC50) values. Strong correlations were found between the average MIC against S. aureus and their phenolic (r = -0.89) and flavonoid content (r = -0.87), reinforcing the possible role of these metabolite classes on the antimicrobial activity of C. spinosa derived extracts. Moreover, CL and CR showed the best inhibitory activity against S. aureus clinical isolates, they also showed synergistic action with oxacillin against all these strains (at least at one combined proportion). These results encourage the identification of active substances which could be used as lead(s) molecules in the development of new antimicrobial drugs.